STUDI KELAYAKAN ASPEK TEKNIS BUDIDAYA TANAMAN BAMBU DI KECAMATAN GOLEWA, KABUPATEN NGADA, PROVINSI NUSA TENGGARA TIMUR - Puspita, Victoria Ayu; Due, Maria Serviana; Djawapatty, David Januarius (Agros Journal of Agriculture Science, 2024)
Bamboo is a non-timber forest product (NTFP) commodity that has high SEE (Social, Economic and Ecological) benefits for meeting community needs and as a soil and water conservation commodity. However, the bamboo population is currently relatively small because bamboo development is still not optimal either by the government or the community, and especially the community thinks that bamboo is only used or exploited by lower class people and has little economic value. Currently, bamboo is used as an industrial tree or commodity with high economic value and industrial demand is relatively high, so its population needs to be increased, especially by the community, because bamboo cultivation is relatively easy and does not require large investments. Basically, the feasibility study for the technical, social and ecological aspects of bamboo cultivation used in this research is to carry out an analysis of the environmental conditions of the bamboo development area in Golewa District, Ngada Regency. This analysis then produces recommendations for the feasibility of developing bamboo cultivation at that location, in this way it will be possible to obtain things that are obstacles in the technical development of bamboo cultivation in Golewa District, Ngada Regency. The results of this research show that technically the development of intensive bamboo cultivation has the potential to be considered feasible because it has human resources that are ready to be trained, good physical infrastructure is available, and communication networks are already available. However, there are several notes to pay attention to, namely that human resources who have knowledge about intensive bamboo cultivation are still limited. It is necessary to carry out continuous counseling and assistance efforts for intensive cultivation and utilize available communication networks by establishing a market information system for bamboo trading.